Fenomena Politik Uang dalam Pemilihan Legislatif di Kabupaten Pali Tahun 2024 - Irmawati; Norma Juainah; Siti Anisyah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2025)
This study discusses the phenomenon of money politics in the 2024 legislative elections in PALI district. This phenomenon creates an interesting dynamic due to the fraud that occurred during the general election. This study uses descriptive qualitative research, which was conducted in Raja Barat village, Tanah Abang sub-district, Penukal Abab Lematang Ilir (PALI) district. The data collected in this study were obtained through interviews with informants, direct field observations, and documentation studies. The purpose of this study is to determine how the phenomenon of money politics occurs in Raja Barat Village, Tanah Abang Subdistrict, PALI District, and to identify the factors that influence the occurrence of money politics in the legislative elections in Raja Barat Village, Tanah Abang Subdistrict, PALI District. The theories used in this study are patronage and clientelism theories, as well as Gabriel Almond's political culture theory, as these theories are considered to provide a foundation for addressing the issues raised in this study. The results of the study indicate that the community accepts the practice of money politics because they are accustomed to receiving money and obtaining money during election periods. The community believes that this has become a tradition or culture practiced by the village community during elections, including local elections and village head elections. The patterns of money politics observed in Raja Barat Village include vote buying and the distribution of personal gifts by legislative candidates or their campaign teams. There are two factors influencing the continued occurrence of money politics: cultural and customary factors, and the second factor is the weakness of oversight and law enforcement. This study contributes to understanding the dynamics of money politics in the context of legislative elections and provides insights into the factors influencing the occurrence of money politics.